The Extent and Nature of Food and Beverage Company Sponsorship of Children's Sports Clubs in Canada: A Pilot Study - Pauzé, Elise; Ekeh, Odera; Potvin Kent, Monique (Université d'Ottawa | University of Ottawa, 2020)
Food and beverage marketing is considered a determinant of childhood obesity. Sponsorship is a marketing technique used by the food industry to target young people when they are engaged in sports. The purpose of this study was to document the frequency and nature of food company sponsorship of children's sports clubs in Ottawa, Canada. Using national data on sports participation, the five most popular sports among Canadian children aged 4-15 years were first selected for inclusion in the study and relevant sports clubs located in Ottawa (Canada) were then identified. Sports club websites were reviewed between September and December 2018 for evidence of club sponsorship. Food company sponsors were identified and classified by food category. Of the 67 sports clubs identified, 40% received some form of food company sponsorship. Overall, sports clubs had 312 commercial and noncommercial sponsors. Food companies constituted 16% of total sponsors and were the second most frequent type of sponsor after sports-related goods, services, and retailers (25%). Fast food restaurants and other restaurants accounted for 45% and 41% of food company sponsors, respectively. Food company sponsorship of children's sports clubs is frequent with some promoting companies or brands associated with unhealthy foods. Policymakers should consider restricting the sponsorship of children's sports clubs by food companies that largely sell or promote unhealthy foods.
Keywords: adolescents; alcohol; children; corporate social responsibility; food marketing; health policy; sponsorship; sports